#### Answer

$y_1 = a*(y_2 - (y_3/2))$
where a is a real number

#### Work Step by Step

For all the three points to lie on a straight line, one point must be a linear combination of the other two. This implies
$(0,y_1) = a\times(1,y_2)+b\times(2,y_2)$
Equating x-coordinates on both sides gives the following relation :
$0 = a + 2*b$
Therefore, $b = -a/2$
Now equate the y-coordinates on both sides of the equation,
$y_1 = a*y_2 + b*y_3$
substituting $b = -a/2$ in the above equation we get
$y_1 = a*(y_2 - (y_3/2))$
where a can be any real number